RANCANG BANGUN MODUL TRAINER KIT MATA KULIAH SISTEM KENDALI+LAB BERBASIS INTERNET OF THINGS (IoT) - Hernandi, William; Rahardjo, Pratolo; Alit Swamardika, Ida Bagus; Divayana, Yoga; Oka Saputra, Komang (Jurnal SPEKTRUM; Vol 11 No 2 (2024): Jurnal SPEKTRUM, 2024)
Along with the development of technology, control systems can now control various devices using smartphones connected to the internet remotely (Internet of Things). In order to have a good understanding of this field, universities have a very important role as an education institution. One of them is Udayana University through the Control System + Lab Course in the Independent Campus Learning Curriculum. This study aims to design an IoT-based Lab + Control System Trainer Kit Module using DevKit ESP32. The designed system includes an IoT-based DC motor control system using an L298N motor driver, an IoT-based water cooling control system using a DS18B20 temperature sensor, and an IoT-based water level control system using an HC-SR04 ultrasonic sensor. The system will be controlled through an application that has been created and installed on a smartphone connected to the internet so that it can be tested and analyzed to draw conclusions.